2021
DOI: 10.2147/copd.s301622
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides SLPI and Beta Defensin-1 in Sputum are Negatively Correlated with FEV1

Abstract: Background Chronic obstructive pulmonary disease (COPD) and asthma have heterogeneous inflammation with inhaled corticosteroids (ICS) as a mainstay of treatment. There is increased prevalence of non-typeable Haemophilus influenzae (NTHi) persistence in airways of patients with neutrophilic airway inflammation, potentially due to suppressed host defence after corticosteroid treatment. Antimicrobial peptides (AMPs) have antimicrobial activity against pathogens and immunomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The lung is consistently exposed to noxious stimuli, including microorganisms. Although there is a controversy regarding which comes first, infections combine with inflammatory and pathological changes in the development of asthma and COPD [ 33 ] and antimicrobial peptides from the airway epithelium have been associated with the pathologic features of both [ 34 , 35 ]. ACO cluster 2 was characterized by the enrichment of dendritic cell-associated C-type lectine-2 (Dectin-2) family and the TLR regulation by endogenous ligands pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The lung is consistently exposed to noxious stimuli, including microorganisms. Although there is a controversy regarding which comes first, infections combine with inflammatory and pathological changes in the development of asthma and COPD [ 33 ] and antimicrobial peptides from the airway epithelium have been associated with the pathologic features of both [ 34 , 35 ]. ACO cluster 2 was characterized by the enrichment of dendritic cell-associated C-type lectine-2 (Dectin-2) family and the TLR regulation by endogenous ligands pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As for antimicrobial proteins and peptides, it has been previously shown that sputum levels of SLPI and elafin display an inverse correlation with bacterial load [228]. In a more recent study in COPD and asthmatic patients [308], an overall negative correlation between both sputum SLPI and hBD-1 and FEV 1 was found. These data highlight the potential for these AMPs to identify patients at greater risk of lung function decline.…”
Section: Copd (Table 3)mentioning
confidence: 90%
“…Other effects described elsewhere include chemotaxis, angiogenesis, wound healing, antitumor, antifungal, antiviral, and less potent antimicrobial activity (279). b-defensins have been implicated in COPD pathogenesis and disease progression (297,315,(375)(376)(377)(378)(379)(380)(381). Reduced lung function has been associated with increased levels of defensins (380,(382)(383)(384).…”
Section: Antimicrobial Peptides and Lung Damage In Microbiomeimmune C...mentioning
confidence: 99%